2022
DOI: 10.1111/jgh.16075
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Lugol‐unstained lesions predict higher cumulative risk of malignance in the esophagus

Abstract: Background and Aim:The impact of the presence of multiple Lugol-unstained lesions (LULs) in the esophagus on the risk of having severe dysplasia and above (SDA) lesions among asymptomatic individuals is unknown. Methods: We collected demographic factors, behavioral variables, and features of LULs from 1073 participants who were biopsied at baseline endoscopic screening in a population-based screening trial, and these individuals were followed over a median time of 7 years. Outcome events were defined as SDA id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 27 publications
(60 reference statements)
0
3
0
Order By: Relevance
“…33 However, our previous studies have shown that nondysplastic Lugol-unstained lesions (ND-LULs) could be the initial stage of ESCC, and endoscopic features of LULs independently indicate the risk of progression of precursor lesions. [34][35][36][37][38] Although we have taken these factors into account in the surveillance of the ESECC trial, the above commonly adopted pathology-based criteria would still have resulted in insufficient surveillance of ND-LULs to some extent, and therefore dilute the screening effect in this trial.…”
Section: Discussionmentioning
confidence: 99%
“…33 However, our previous studies have shown that nondysplastic Lugol-unstained lesions (ND-LULs) could be the initial stage of ESCC, and endoscopic features of LULs independently indicate the risk of progression of precursor lesions. [34][35][36][37][38] Although we have taken these factors into account in the surveillance of the ESECC trial, the above commonly adopted pathology-based criteria would still have resulted in insufficient surveillance of ND-LULs to some extent, and therefore dilute the screening effect in this trial.…”
Section: Discussionmentioning
confidence: 99%
“…Discrepancies were resolved by discussion. Based on review of the literature and our previous study results, we assessed 6 endoscopic features in this study, including the size of LULs, mosaic staining, irregularity, sharpness of the border, dark staining border, and numbers of LUL in the entire esophagus 14,18,19 . The features were extracted from the LUL with the highest grade pathologic diagnosis if more than one LUL were found in the esophagus.…”
Section: Methodsmentioning
confidence: 99%
“…Based on review of the literature and our previous study results, we assessed 6 endoscopic features in this study, including the size of LULs, mosaic staining, irregularity, sharpness of the border, dark staining border, and numbers of LUL in the entire esophagus. 14,18,19 The features were extracted from the LUL with the highest grade pathologic diagnosis if more than one LUL were found in the esophagus. Details regarding the measurements of endoscopic features of LULs are presented in the supplementary material (supplementary material: definition and Figure S1).…”
Section: Endoscopic Image Reviewmentioning
confidence: 99%